ON THE CORRELATION OF MANAGEMENT THEORY AND METHODOLOGY - A. V. Raychenko (Вестник университета)
An alternative approach to the study of the relationship between methodology and management theory has been presented. Based on the classical understanding of the categories under consideration, a new format for constructing scientific representations has been proposed, in which the theory is necessarily based on the formulation and application of a certain methodology. The format presented by the publication allows us not only to substantiate fundamentally the theory of management, but also to ensure its constructive positioning in the general system of knowledge based on the universality of the methodology. The development of the research presented by the publication will enable to discover fundamentally new opportunities for scientific substantiation and construction in management and other swiftly developing areas of knowledge and activities.